Evaluation of X-ray spectra transmitted by different concrete compositions. (November 2015) - Costa, P.R.; Vieira, D.V.; Naccache, V.K.; Ferreira, K.R.; Priszkulnik, S.
Abstract: Additional shielding material must frequently be incorporated to medical facilities in order to comply with radiation protection requirements when using radiation sources. Typical materials for shielding walls, floor and ceiling are the lead, concrete and barite. In the present work, a group of four concrete compositions was evaluated by using broad beam transmission curves and transmitted spectra in the range of X-ray energies used for diagnostic imaging. The studied concretes were classified as ordinary concrete (Type C), concrete with addition of hematite (Types H1 and H2) and concrete with addition of steel grit (Type S). Concrete with steel grit shows be more efficient as shielding material of the three heavy types concrete studied. The two mixes of concrete and hematite are practically equivalent from the radioprotection point of view. However, the granulation difference between them might be important to other fields, as shielding is not the only function of concrete in the building structure. Although they are not as efficient as concrete with steel grit, they may be a shielding option in a facility with low shielding requirement. Highlights: X-ray transmission data and spectra through four different concrete types were measured. The X-ray tube voltages were selected within the diagnostic range (60–150 kV). Concrete with steel grit was found to be the best for shielding among the samples. High-attenuation concretes shows be an alternative shielding material for high-workload imaging facilities.